The diffusion of the ISO-9001 and firm performance: The Case of Morocco - Taouab, Omar (Archives of Business Research, 2016)
The paper’s objectives is to determine the variables that have a significant impact on the diffusion of the ISO 9001 and its impact on the performance of the Moroccan companies of the textile-clothing industry. After a review of the literature on the variables which justify the diffusion of this tool, we tested our hypothesis of research. An empirical study was carried out using a sample of 45 ISO certified firms. Data were obtained from the quality managers of the companies through a questionnaire. A regression logistic model is also applied in order to determine the impact of variables that impact the diffusion of ISO quality and their impact on the performance’s firms. Our principal findings show that variables of contingency, such as: the size of the companies, turbulence, the pressure of the environment, the strategy and the implication of the employees, play a very important part in the diffusion of the ISO 9001.